Rekayasa Perangkat Lunak dalam Pendidikan Pesantren - Habibullah, Ricky; Sugiantoro, Bambang (Lembaga Sosial Rumah Indonesia, 2023)
The rapid development of technology in recent years has also impacted the education sector, especially in pesantren institutions. Pesantren has responded well to technological advances by utilizing the Maktabah Syamilah (application) of online book libraries as an educational tool, allowing students to access yellow book references. This study aims to demonstrate that software engineering technology (RPL) that dynamically develops has an important role in the development of Pondok Pesantren in implementing teaching instruments. This study uses the library research method, supported by literature evidence, to compile the research. The results show that software development must go through a structured process and have many models, namely software engineering (RPL), which aims to improve the software. This research implies that the current pattern of pesantren education utilizes technology as a learning instrument, such as Maktabah Syamilah, allowing teachers and students to respond well to technological advancements.